2020
DOI: 10.28991/cej-2020-03091465
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Economic Analysis of Selected Pavement Preservation Treatments

Abstract: Pavements are one of the highest assets and represent massive investment. The need to design and provide a sustainable maintenance service is becoming a priority and this comes mutually with the intentions to reduce impacts caused by maintenance treatments to the environment. This paper through a case study presents a Life Cycle Cost and Assessment technique during a 30 year analysis period to measure the cost effectiveness, embodied energy and carbon emissions of selected preservation treatments. These treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Economic reforms are a source stabilizing the financial market, the trust of investors and people restores if any type of reforms prevail in an economy so green technology will flourish the economy. The findings of the studies [ 8 , 9 , 14 – 16 , 19 , 59 , 60 ] convey that institutions have crucial importance for environmental performance. Based on the findings of the study, it is highlighted that economic and political reforms are both crucial for environmental protection in developing countries.…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
“…Economic reforms are a source stabilizing the financial market, the trust of investors and people restores if any type of reforms prevail in an economy so green technology will flourish the economy. The findings of the studies [ 8 , 9 , 14 – 16 , 19 , 59 , 60 ] convey that institutions have crucial importance for environmental performance. Based on the findings of the study, it is highlighted that economic and political reforms are both crucial for environmental protection in developing countries.…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
“…According to the BP Statistical Review of World Energy, China has been the world’s fastest-growing energy consumer for 19 consecutive years [ 3 ] and accounts for 29% of the world’s total carbon emissions [ 4 ]. Although carbon emissions show a certain positive association with economic growth [ 5 ], the large amount of carbon emissions will not only impact the climate [ 6 ], but also human health. Previous studies have shown that carbon dioxide can cause harm to human health through inhalation and skin contact [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these countries found laws and policies to control, monitor and reduce environmental pollution, they fail to enforce them to protect the environment. Additionally, in the developing countries, the water supply systems are inadequate and delivered low water quality that resulted from water demand increases rapidly and discharges the untreated wastewater direct to the freshwater sources (Awoke et al, 2016;Zulu et al, 2020). WHO, 2017 stated that municipal water supply system must deliver safe and clean water (i.e., water does not have living microorganisms or harmful chemical substances in concentrations more than the acceptable limit).…”
Section: Public Interest Statementmentioning
confidence: 99%